RESEARCH DATA COLLECTION - Daruhadi, Gagah; Sopiati, Pia (Ridwan Institute, 2024)
This research examines data collection methods in quantitative and qualitative approaches, with a focus on in-depth understanding of the data collection, analysis and validation processes. The main objective of this study is to increase understanding of effective data collection techniques and identify methods that can increase the validity and reliability of research data. The methodology applied is a literature study, which involves theoretical analysis of data collection techniques, research instruments, and data validity. The research results show significant differences in data collection methods between quantitative and qualitative research, each with its advantages and disadvantages. The study's conclusion emphasizes the importance of selecting appropriate data collection methods to ensure data validity, which is crucial for analysis in follow-up studies.